Foreign direct investment and democratic survival: a sectoral approach. Issue 2 (17th February 2022) - Kim, Nam Kyu
ABSTRACT: How do foreign direct investment (FDI) inflows affect democratic survival? No study has examined how FDI influences the likelihood of democratic survival, although many studies have studied the effect of regime type on FDI inflows. The previous finding that FDI contributes to authoritarian survival and decreases prospects for democratization does not answer this question since determinants of democratic transitions are clearly distinct from those of democratic survival. I argue that FDI in non-primary sectors is more likely than FDI in primary sectors to contribute to democratic survival since non-primary FDI is likely to produce growth-enhancing effects through upstream and downstream linkages in the host economy and facilitate the diffusion of democratic ideas and norms originating from the West. To overcome the problem of the sectoral FDI data's poor coverage, I exploit an exogenous variation in FDI inflows by utilizing a country's geographical distance from developed economies. Using a sample of democracies from 1970 to 2010, I find that inward FDI, instrumented by market proximity to developed economies, is associated with an increased likelihood of democratic survival. The analysis of primary and non-primary FDI also provides supporting evidence.